Cultural Diversity and Spiritual/Religious Health Care of Patients with Cancer at the Dominican Republic - Héctor E Lopez-Sierra (Elsevier, 2019)
Objective: Noncommunicable diseases have become a global pandemic with disproportionately higher rates in low-and middle-income countries. Dominican Republic (DR) as a Latin Americans and Spanish-speaking Caribbean developing country shares a socioculturally distinctive spiritual and religious pattern. It underlines their attitudes, values, and belief systems, socioeconomic reality, and racial attitudes. Social sciences and religious studies suggest that a relationship between spirituality, religion, health-care services (Sp/Re-HCS), and cultural diversity exists. This article argues in favor of a descriptive historical analysis of that relationship. Methods: Systematic search of academic articles, abstracts, and conclusions published in Medline, EBSCO, PsycINFO (OVID), ATLA Religion Database, and Google Scholar was undertaken using a combination of English and Spanish relevant terms. The analysis of articles was examined through a historical background approach, a systematic review, and a content analysis. Results: A Roman Catholic organization, Voluntariado Jesús con los Niños Foundation, serves to cancer patients that have almost no financial protection. The Dominican Evangelical Church (DEC) founded in 1932 a medical service base at the International Hospital in Santo Domingo (IHSD). When the DR government developed medical services, the DEC closed the IHSD. Since then, there is no any DR Evangelical or Protestant organization that offers Sp/Re-HCS to cancer patients (S/R-HCSCP). Conclusions: This analysis suggests that a relationship between S/R-HCS and cultural diversity exists. In this sociohistorical analysis, the nonhomogeneous cultural distinctiveness of the Sp/Re-HCS has been demonstrated through the analytical description of the only one organization of S/R-HCSCP at DR.